A novel approach to improve the energy and cost efficiency of feedstock drying for pellet production. (15th April 2021) - Paczkowski, Sebastian; Labbé, Rodrigo; Sauer, Christian; Anetzberger, Anja; Russ, Michael; Wöhler, Marius; Jaeger, Dirk; Pelz, Stefan
Highlights: A new pellet production process is investigated based on sieving before drying. Large moist particles (24% wc) and dry fines (12% wc) are pressed at different proportions. Pellets showed improved or acceptable physical properties. Production costs and energy consumption strongly decreased with increasing sieve size Optimum quality, emissions and cost savings was a 0.4 moist / dry fiber ratio (2.0 mm mesh sieve). Abstract: The success of the pellet industry depends on internal and external factors, comprising pellet quality, pellet production parameters and market variables. This study investigated the pellet production process from the raw material properties to the economic production parameters in order to quantify the feasibility of a new production concept. The proposed concept includes the sieving of the wet feedstock and successive selective drying of the fine fraction, while the coarse fraction is not dried. The impact of this energy saving measure is evaluated in terms of pellet quality, combustion emissions, and production / transport costs and energy consumption. Three sieve sizes were investigated (1.4 mm, 2.0 mm, 2.8 mm). The feedstock was separated and the fine and coarse fraction were equilibrated at 12 and 24% water content, respectively and mixed again for pelletization in a semi-industrial ring dye press. The pellets showed an improved durability and a higher water content, which had both positive and negative impacts on the combustion emissions. The bulk density decreased, which affected the transport parameters negatively. The economic benefit for medium and large scale production was high, mainly depending on the feedstock water content and the thermal efficiency of the dryer. The 2.0 mm sieve caused the best combination of improved durability, reduced emissions, increasing transport costs and thermal energy savings. A post-press reduction of the pellet water content can further improve the pellet quality and reduce combustion emissions, while the process of wet sieving has to be evaluated on industrial scale.